Lower irritation microemulsion-based rotigotine gel: formulation optimization and in vitro and in vivo studies - Wang Z (Dove Medical Press, 2015)
Zheng Wang,1 Hong-Jie Mu,1 Xue-Mei Zhang,1 Peng-Kai Ma,1 Sheng-Nan Lian,1 Feng-Pu Zhang,1 Sheng-Ying Chu,1 Wen-Wen Zhang,1 Ai-Ping Wang,1,2 Wen-Yan Wang,2 Kao-Xiang Sun1 1School of Pharmacy, Yantai University, 2State Key Laboratory of Long-acting and Targeting Drug Delivery System, Yantai, Shandong Province, People’s Republic of China Background: Rotigotine is a potent and selective D1, D2, and D3 dopaminergic receptor agonist. Due to an extensive first-pass effect, it has a very low oral bioavailability (approximately 0.5% in rats).Purpose: The present investigation aimed to develop a microemulsion-based hydrogel for transdermal rotigotine delivery with lower application site reactions.Methods: Pseudoternary phase diagrams were constructed to determine the region of oil in water (o/w)-type microemulsion. Central composite design was used to support the pseudoternary phase diagrams and to select homogeneous and stable microemulsions with an optimal amount of rotigotine permeation within 24 hours. In vitro skin permeation experiments were performed, using Franz diffusion cells, to compare rotigotine-loaded microemulsions with rotigotine solutions in oil. The optimized formulation was used to prepare a microemulsion-based hydrogel, which was subjected to bioavailability and skin irritancy studies.Results: The selected formulations of rotigotine-loaded microemulsions had enhanced flux and permeation coefficients compared with rotigotine in oil. The optimum microemulsion contained 68% water, 6.8% Labrafil®, 13.44% Cremophor® RH40, 6.72% Labrasol®, and 5.04% Transcutol® HP; the drug-loading rate was 2%. To form a microemulsion gel, 1% Carbomer 1342 was added to the microemulsion. The bioavailability of the rotigotine-loaded microemulsion gel was 105.76%±20.52% with respect to the marketed rotigotine patch (Neupro®). The microemulsion gel irritated the skin less than Neupro.Conclusion: A rotigotine microemulsion-based hydrogel was successfully developed, and an optimal formulation for drug delivery was identified. This product could improve patient compliance and have broad marketability. Keywords: pseudoternary phase diagrams, central composite design, transdermal